Vulnerability of RC hammer head type bridge piers under seismic induced P-delta effect and simultaneously strength and stiffness degrading hysteretic behaviour - Chowdhury, Pronoy Roy (Journal of Structural Engineering, 2024)
Current philosophy of seismic design is performance based seismic design, where some degree of inelastic behaviour is permitted due to inherent redundancy and reserve strength present in a structure. Reinforced concrete hammer head bridge piers represents inverted pendulum category of structure. On virtue of their structural configuration such structures are more vulnerable to topple down under earthquake induced strong ground acceleration. Plasticization of structural materials may take place at critical junctions like hammer head portion and the relatively slender stalk portion under consecutive yield excursions. Lateral deflection of the slender stalk portion of the pier is increased causing time progressive P-Δ effect, over each cycle. As such lateral deflection gets increased progressively and overturning tendency is aggravated continually until the structure topples down. This study is an attempt to demonstrate through an example problem, the judicious range upto which inelastic behaviour may be permitted in case of performance based design of hammer head type of bridge piers subjected to seismic activity. As such this work may serve as a guidance for striking a critical balance between safety and economy for practicing designers in case of performance based seismic design of structures such as bridge piers.